Differentiation of mouse embryonic stem cells and their hybrids during embryoid body formation - Mittmann,Josane (2002)
We studied the karyotypes of three hybrid clones of mouse embryonic stem cells and murine splenocytes (two having near diploid and one having near tetraploid chromosome numbers) and the characteristics of their differentiation during the formation of embryoid bodies. The X chromosome originating from embryonic stem cells may be lost in hybrids with a near diploid chromosome number and reprogramming of the "somatic" X may occur. The morphological data we obtained using light and electron microscopy revealed a correlation between the karyotype constitution of hybrid cells and their differentiation during the formation of embryoid bodies. At the beginning of development, the embryoid bodies derived from hybrid cells already showed an advanced degree of differentiation. The production of significant quantities of cartilage was typical for hybrid cells with near tetraploid chromosome numbers. The hybrid cells showed restricted pluripotent capacity and were already committed when they started to differentiate into embryoid bodies.